The Influence of Auditory Information on Visual Size Adaptation - Tonelli, Alessia; Cuturi, Luigi F.; Gori, Monica (Frontiers in Neuroscience, 2017)
Size perception can be influenced by several visual cues, such as spatial (e.g. depth or vergence) and temporal contextual cues (e.g. adaptation to steady visual stimulation). Nevertheless, perception is generally multisensory and other sensory modalities, such as auditory, can contribute to the functional estimation of the size of objects. In this study, we investigate whether auditory stimuli at different sound pitches can influence visual size perception after visual adaptation. To this aim, we used an adaptation paradigm (Pooresmaeili et al., 2013) in three experimental conditions: visual-only, visual-sound at 100 Hz and visual-sound at 9000 Hz. We asked participants to judge the size of a test stimulus in a size discrimination task. First, we obtained a baseline for all conditions. In the visual-sound conditions, the auditory stimulus was concurrent to the test stimulus. Secondly, we repeated the task by presenting an adapter (twice as big as the reference stimulus) before the test stimulus. We replicated the size aftereffect in the visual-only condition: the test stimulus was perceived smaller than its physical size. The new finding is that we found the auditory stimuli have an effect on the perceived size of the test stimulus after visual adaptation: low frequency sound decreased the effect of visual adaptation, making the stimulus perceived bigger compared to the visual-only condition, and contrarily, the high frequency sound had the opposite effect, making the test size perceived even smaller.